2011
DOI: 10.1177/0363546510392326
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Concussion Incidence in High School Sports

Abstract: Although the collision sports of football and boys' lacrosse had the highest number of concussions and football the highest concussion rate, concussion occurred in all other sports and was observed in girls' sports at rates similar to or higher than those of boys' sports. The increase over time in all sports may reflect actual increased occurrence or greater coding sensitivity with widely disseminated guidance on concussion detection and treatment. The high-participation collision sports of football and boys' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
428
5
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(453 citation statements)
references
References 12 publications
15
428
5
5
Order By: Relevance
“…42 Young athletes of both sexes are at risk of concussion, but girls report higher concussion rates than boys, particularly in high school and college soccer, basketball, and baseball or softball. 28,[43][44][45] The factors that account for these differences remain uncertain, but might include quality of protective gear, recognition and reporting of concussion symptoms, and neck length and neck muscle strength. 46 Differences in recovery trajectories between males and females are also poorly understood.…”
Section: Recoverymentioning
confidence: 99%
“…42 Young athletes of both sexes are at risk of concussion, but girls report higher concussion rates than boys, particularly in high school and college soccer, basketball, and baseball or softball. 28,[43][44][45] The factors that account for these differences remain uncertain, but might include quality of protective gear, recognition and reporting of concussion symptoms, and neck length and neck muscle strength. 46 Differences in recovery trajectories between males and females are also poorly understood.…”
Section: Recoverymentioning
confidence: 99%
“…Stoller et al 16 reported that half of family practice and emergency department physicians had no knowledge of any consensus statement related to concussion in sport, whereas others discuss underreporting of concussion injuries. 1,2,4 This underscores the importance of having adequately trained staff present or readily available to athletes during times of practice and competition, especially for female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 50% of the concussions may go unreported. 1,2 A Joint Commission of the American Academy of Neurology, American Neurology Society, and Child Neurology Society report describes an ethical obligation to protect the athletes' current and future physical and mental health while informing athletes, parents, and medical professionals about the risks of concussion and postconcussive impairments. 3 Although some agreement exists, diagnosis and management of concussion are continually evolving as new data become available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all sports, the rate increased from 0.23 concussions per 1000 athlete-exposures (AEs) to 0.51. In another study of high school sports concussions from a single school district, Lincoln et al demonstrated an increase from 0.12 concussions per 1000 AEs in 1997-1998 to 0.49 in the 2007-2008 school year [3]. Possible explanations for these findings include an actual increase in the frequency of the injury vs increased reporting of injury because of heightened awareness of participants, parents, coaches, and medical staffs and improved reporting mechanisms.…”
Section: Epidemiologymentioning
confidence: 99%